Identities concerning k-balancing and k-Lucas-balancing numbers of arithmetic indexes - Prasanta Kumar Ray (AIMS Mathematics, 2019)
In this article, we derive some identities involving k balancing and k-Lucas-balancing numbers of arithmetic indexes, say an + p, where a and p are some fixed integers with 0≤p≤a-1.